PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN SEBELUM COVID-19 DAN PADA MASA COVID-19 - Gunawan, Felicia Hartanti (Media Akuntansi dan Perpajakan Indonesia, 2021)
This study aims to compare the company's financial performance as measured by financial ratios (profitability ratios, liquidity ratios, solvency ratios, and activity ratios.) The method used in this research is descriptive statistics with secondary data collection from the 2019 and 2020 quarterly financial reports. Sampling using the purposive sampling method and the sample in this study were 23 food and beverage sector companies listed on the IDX in 2019 and 2020. The normality test in This study used the Kolmogorov-Smirnov method and it was concluded that the data were not normally distributed so that the non-parametric Wilcoxon signed rank test was used. The results of this study indicate that of the four financial ratios, the one that had a significant difference before and during the pandemic were profitability ratio and liquidity ratio. Meanwhile, based on the analysis of solvency ratio and activity ratio, it shows that there were no significant differences before and during the Covid-19 pandemic.